Determinan Niatan Penyalahgunaan Dana Desa Perspektif Fraud Diamond - Pahmi Ardi; Suharman Suharman; U. Ari Alrizwan (Universitas Teuku Umar, 2026)
This research examines the factors diving behavioral intentions toward the missaproriation of village funds across semparuk district, utilizing financial pressure, internal control systems, organizational culture, and the capability of human resources as variables within the framework of the Fraud Diamond Theory. This research employs a quantitative approach. The sample includes people directly involved with Semparuk District village fund management. Data analysis was conducted using SPSS 30, encompassing validity and reliability tests, classical assumption tests normality, multicollinearity, and heteroscedasticity, as well as hypothesis testing through multiple linear regression analysis, t-tests, and the coefficient of determination. The results indicate that financial pressure, internal control systems, and the capability of human resources have a significant influence on the intention to misappropriate of village funds. Conversely, organizational culture does not show a significant influence on the intention to misappropriate of village funds. This study is limited by its sole reliance on the fraud diamond theory, its focus on the village government scale, and the four variables utilized. Future research may expand upon the theories and variables used, such as incorporating external pressure and organizational position.